Roman Emperors in Context : Theodosius to Justinian - Croke, Brian (Variorum Collected Studies, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- List of figures -- Acknowledgements -- List of abbreviations -- Introduction: historicising imperial business -- 1 Reinventing Constantinople: Theodosius I's imprint on the imperial city -- 2 Dynasty and aristocracy in the fifth century -- 3 Dynasty and ethnicity: emperor Leo I and the eclipse of Aspar -- 4 Leo I and the palace guard -- 5 The imperial reigns of Leo II -- 6 Ariadne Augusta: shaping the identity of the early Byzantine empress -- 7 Justinian under Justin: reconfiguring a reign -- 8 Justinian, Theodora and the Church of Saints Sergius and Bacchus -- 9 Justinian the 'sleepless emperor' -- 10 Justinian's Constantinople -- Bibliography -- Index.